In flow acoustic characterisation of a 2D active liner with local and non local strategies. (30th March 2022) - Billon, K.; Bono, E. De; Perez, M.; Salze, E.; Matten, G.; Gillet, M.; Ouisse, M.; Volery, M.; Lissek, H.; Mardjono, J.; Collet, M.
Abstract: The design and the grazing flow aeroacoustical characterization of a 2D active liner based on an array of electroacoustic absorbers are presented in this paper. The strategy stands on a pressure-based, current-driven digital architecture for impedance control with both local and non local architectures. A wind tunnel test rig is used for the in-flow experimental validation. The stability and robustness of the whole system are investigated as a function of flow velocity showing the efficiency of the proposed approached. The air flow slightly reduces the efficiency while maintaining the adaptability and the stability, and better performances are obtained with the non local control strategy.